PERATURAN MAHKAMAH AGUNG NOMOR 1 TAHUN 2016 TENTANG PROSEDUR MEDIASI DI PENGADILAN PERSPEKTIF HUKUM ISLAM - Libriyanti, Oktavina (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2017)
Mediation  is a process of problem-solving negotiations, where impartial  parties  work  with disputants to seek mutual  consent. Mediation  is also  known  in Islamic  law  that  equates mediation with  islah  or Al-Sulh, is a process  of dispute resolution in which  the parties  agree  to end  their case  peacefully. The provisions  of mediation in the last Court are regulated in supreme Court Regulation  number 1 of 2016. Regulation  Court are one of the courts  under  the Supreme Court in accordance with the mandate of constitution, therefore it is obligatory to enforce the provisions  of mediation set forth in the Supreme Court Regulation.  In accordance with its authority in terms of solving a particular dispute for Muslims, it means that the Religious Court, besides deriving from the positive law of Indonesia, must  also derive from Islamic law. Likewise with the provisions on the implementation of mediation in the Court, in addition  to following the Supreme Court, in addition  to following the Supreme Court Regulation number 1 year 2016, also follow the provisions of mediation set forth in Islamic Law.  Based on the above  background this research reveal issues,  what is the view of Islamic law in mediation procedures in religious court.